Identification of Genetic Mutations in Cancer: Challenge and Opportunity in the New Era of Targeted Therapy - Jin, Jing; Wu, Xu; Yin, Jianhua; Li, Mingxing; Shen, Jing; Li, Jing; Zhao, Yueshui; Zhao, Qijie; Wu, Jingbo; Wen, Qinglian; Cho, Chi Hin; Yi, Tao; et al. (Frontiers in Oncology, 2019)
The introduction of targeted therapy is the biggest success in the treatment of cancer in the past few decades. However, heterogeneous cancer is characterized by diverse molecular alterations as well as multiple clinical profiles. Specific genetic mutations in cancer therapy targets may increase drug sensitivity, or more frequently result in therapeutic resistance. In the past three years, several novel targeted therapies have been approved for cancer treatment, including drugs with new targets (i.e., anti-PD1/PDL1 therapies and CDK4/6 inhibitors), mutation targeting drugs (i.e., the EGFR T790M targeting osimertinib), drugs with multiple targets (i.e., the EGFR/HER2 dual inhibitor neratinib) and drug combinations (i.e., encorafenib/binimetinib and dabrafenib/trametinib). In this perspective, we focus on the most up-to-date knowledge of targeted therapy and describe how genetic mutations influence sensitivity of targeted therapy, highlighting the challenges faced with in this era of precision medicine. Moreover, the strategies dealing with mutation-driven resistance are further discussed. Advances in these areas would allow for more and more targeted and effective therapeutic options for cancer patients.